2017
DOI: 10.1007/s11418-017-1111-8
|View full text |Cite
|
Sign up to set email alerts
|

Two flavone C-glycosides as quality control markers for the manufacturing process of ephedrine alkaloids-free Ephedra Herb extract (EFE) as a crude drug preparation

Abstract: As part of our continuing study of ephedrine alkaloids-free Ephedra Herb extract (EFE) in pursuit of its approval as a crude drug preparation, we identified two quantitative markers for the quality control of the manufacturing process of EFE and sought to establish cost-effective and simple methods for quantitative analyses. We analysed Ephedra Herb extracts grown in different habitats and collection years by liquid chromatography/high-resolution mass spectrometry (LC/HRMS) and detected two notable peaks commo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 5 publications
0
9
0
Order By: Relevance
“…Molecules 2020, 25, x; doi: FOR PEER REVIEW www.mdpi.com/journal/molecules the sweating generated by the ingest of E. sinica Stapf that could be attributed to compounds such as mahuannins B ( 93) and F (97), and also to ephedrannin A ( 98) [92]. In this context, vicenin 2 (66), isovitexin 2"-O-rhamnoside (64) and apigenin (52) have been evaluated as quality control markers for the manufacturing process of Ephedra Herb extract (EHE) [93].…”
Section: Amino Acid Derivativesmentioning
confidence: 99%
See 1 more Smart Citation
“…Molecules 2020, 25, x; doi: FOR PEER REVIEW www.mdpi.com/journal/molecules the sweating generated by the ingest of E. sinica Stapf that could be attributed to compounds such as mahuannins B ( 93) and F (97), and also to ephedrannin A ( 98) [92]. In this context, vicenin 2 (66), isovitexin 2"-O-rhamnoside (64) and apigenin (52) have been evaluated as quality control markers for the manufacturing process of Ephedra Herb extract (EHE) [93].…”
Section: Amino Acid Derivativesmentioning
confidence: 99%
“…Likewise, several EFE extracts from plants grown in different habitats and collected over a 12 year period of time were analyzed trough liquid chromatography coupled to high resolution mass spectrometry (LC/HRMS), showing two common notable corresponding to the flavone C-glycosides: vicenin 2 (66) and isovitexin 2"-O-rhamnoside (64). Therefore, they then served as quantitative markers for the quality control of the manufacturing process of the extract [93].…”
Section: Marker Compounds For the Quality Control Of The Manufacturing Process Of Ephedrine Alkaloids-free Ephedra Herb Extracts (Efe's)mentioning
confidence: 99%
“…However, ephedrine alkaloids, 6-hydroxykynurenic acid, and 6-methoxykynurenic acid were not present in the EFE chromatogram. Later, in 2018, Oshima et al [108] analyzed Ephedra herb extracts grown in different habitats and collection years in Japan by liquid chromatography/high-resolution mass spectrometry (LC/HRMS). ese authors detected two notable peaks common to each extract.…”
Section: Recent Applications Of High-resolution Mass Spectrometry For Ephedra Extract Characterizationmentioning
confidence: 99%
“…Quantitative analyses using the isocratic condition of LC/MS showed that the content percentages of 1 and 2 in EFE were 0.140-0.146% and 0.350-0.411%, respectively. Furthermore, Oshima et al [108] analyzed apigenin (3), an aglycon common to 1 and 2. In 2016, Mei et al [110] reported that the HPLC analysis determined five activity components of Ephedra-Gypsum extract.…”
Section: Recent Applications Of High-resolution Mass Spectrometry For Ephedra Extract Characterizationmentioning
confidence: 99%
“…For example, vicenin-2 is a flavone C -glycoside found in diverse plants including Orchidaceae ( Figure 1 a) [ 7 , 8 , 9 ] and has shown various biological activities, including anticancer [ 10 ], anti-inflammatory [ 11 ], and antioxidant effects [ 12 ]. As a result, recent studies on vicenin-2 have focused on various aspects from the quality control of herbal medicine [ 13 ] to organic synthesis [ 14 , 15 ] to the treatment [ 10 ] or prevention [ 16 ] of prostate cancer.…”
Section: Introductionmentioning
confidence: 99%